DIETARY INCLUSION OF VITAMIN E AND SELENIUM ON EGG PRODUCTION, EGG QUALITY AND ECONOMICS OF JAPANESE QUAIL LAYERS - P. Chitra; S. C. Edwin; M. Moorthy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study was conducted to assess the effect of dietary supplementation of vitamin E and selenium on productive performance of Japanese quail layers. This trial was conducted in 210 female Japanese quail birds from seven to twenty six weeks of age. Experimental birds were randomly divided into seven groups viz.T1- Control:  Basal diet (standard Japanese quail ration), T2 Basal diet with  Vitamin E 150mg/kg, T3 Basal diet  with  Vitamin E 300 mg/kg, T4 Basal diet  with  selenium 0.3mg/kg, T5 Basal diet  with selenium 0.6mg/kg,T6 Basal diet with combination of Vitamin E150mg/kg and selenium 0.3mg/kg, T7 Basal diet with combination of Vitamin E and selenium 0.6mg/kg. Dietary supplementation with the different levels of Vitamin E and selenium indicated significantly improved body weight, better feed efficiency and livability when compared to unsupplemented group. During the laying   period the data on hen housed egg production and hen day egg production showed significant increase in egg production from 7 to 26 weeks of age by supplementation of Vitamin E and Seleniumin the Japanese quail.